2021
DOI: 10.1111/psyp.13923
|View full text |Cite
|
Sign up to set email alerts
|

EEG evidence for enhanced attentional performance during moderate‐intensity exercise

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 128 publications
(173 reference statements)
0
7
0
Order By: Relevance
“…However, given that we balanced the target and distractor eccentricities across trials, any “eccentricity” effects should not systematically influence our results. Of note, however, our semi‐linear search arrays made it impossible to examine for lateralized target‐ or distractor‐referenced effects with a distractor or, respectively, target placed on the vertical midline (as is common in the relevant EEG literature; e.g., Dodwell et al, 2021; Hickey et al, 2009). Further, given the many relative placements of the target and distractor that were possible in principle in our semi‐linear arrays (placement of the two stimuli at different eccentricities on either the same or on opposite sides), we limited these to arrangements with a target and distractor on opposite sides, to make the experiment manageable in terms of the number of trials required for EEG analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, given that we balanced the target and distractor eccentricities across trials, any “eccentricity” effects should not systematically influence our results. Of note, however, our semi‐linear search arrays made it impossible to examine for lateralized target‐ or distractor‐referenced effects with a distractor or, respectively, target placed on the vertical midline (as is common in the relevant EEG literature; e.g., Dodwell et al, 2021; Hickey et al, 2009). Further, given the many relative placements of the target and distractor that were possible in principle in our semi‐linear arrays (placement of the two stimuli at different eccentricities on either the same or on opposite sides), we limited these to arrangements with a target and distractor on opposite sides, to make the experiment manageable in terms of the number of trials required for EEG analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that, as a result of statistical learning, participants acquired a strong memory “prior” where the most salient, and in terms of behavioral decision‐making, most significant item (the target on target‐only trials or the distractor on target‐plus‐distractor trials) is likely to appear in the display, and this prior then top‐down biased attentional selectivity towards this location. Previous work has linked the early N1pc and Ppc/Pd to the registration of an “attend‐to‐me” signal and attentional orienting to salient display items (Dodwell et al, 2021; Donohue et al, 2018; Itthipuripat et al, 2014; Johannes et al, 1995; Sawaki & Luck, 2010; Schettino et al, 2016), or to (proactive) suppression of task‐irrelevant distractors (Kerzel & Burra, 2020; Sawaki & Luck, 2010). In the present study, however, the initial lateralized activity is likely to reflect an (as a result of statistical) acquired bias in spatial attention.…”
Section: Discussionmentioning
confidence: 99%
“…The early posterior‐contralateral negativity (N1pc), emerging 120 to 180 ms after stimulus onset, has been considered to reflect early sensory registration of and/or orienting to a salient object or (non‐reportable) exogenous cue (Dodwell et al, 2021; Itthipuripat et al, 2014; Johannes et al, 1995; Schettino et al, 2016). However, in the same time window, a posterior‐contralateral positivity (Ppc) may arise, for instance, when a salient stimulus (e.g., a square) that moves around a circle unexpectedly changes its shape (to a diamond) at the final, lateralized location, violating an “object‐continuity” expectation (Baker et al, 2022); or when, in the additional‐singleton paradigm, a salient but task‐irrelevant (and so to‐be‐ignored or “suppressed”) distractor appears lateralized (in the presence of a non‐lateralized target), in which case the positivity is referred to as P D (Kerzel & Burra, 2020; Sawaki & Luck, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the intensity effect interacts with the term of exercise ( Roig et al, 2013 ). For example, Dodwell and colleagues found benefits of moderate acute exercise on CDA ( Dodwell et al, 2019 ) and on attentional processing ( Dodwell et al, 2021 ), whereas no effect of vigorous acute exercise was observed ( Dodwell et al, 2021 ). Exercise performed immediately prior to a visual perceptual learning task even impairs learning ( Connell et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%